Effect of Water Restriction and Rehydration on HaematoBiochemical, Enzymatic and Hormonal Activity of Hoggets during Summer Season - Patel, Nitin R.; Modi, Rakesh J.; Islam, Manzarul; Wadhwani, Kishan N. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Present experiment was conducted with the objective to study the effect of water restriction and rehydration on haemato-biochemical, hormonal and enzymatic activity of indigenous sheep under intensive production system. Eighteen farm born unshorn hoggets (25-30 kg) of Patanwadi and Marwari breeds were randomly distributed in to three treatment groups on the basis of body weight comprising of six in each group viz., T1 Control (ad libitum water), T2 (20% water restriction) and T3 (40% water restriction). The experiment was conducted in summer season for 30 days i.e. 28 days of water restriction and 2 days of rehydration phase. The feed, in accordance with physiological and production needs of the animals, was offered twice a day (09:00 and 18:00 hrs). Water intake was recorded thrice a day (09:00, 14:00 and 19:00 hrs) and blood samplings was done on day 0, day 28 and after 48 hrs of rehydration. The values of haemoglobin, were significantly decreased, while, serum urea, uric acid, alkaline phosphatase, creatinine phosphokinase, cortisol, triiodothyronine and aldosterone were significantly (p <0.05) increased in water restricted groups of animals on 28th day, with significant improvement in values on 48 hrs of rehydration in most of the traits. However, the decrease in glucose was non-significant between 0 and 28 days and no change was noted in thyroxin levels due to water restriction or rehydration. It indicated that water restriction resulted significant changes in blood variables of hoggets. Blood variables recovered significantly after 48 hr of rehydration, but the serum cortisol, urea, AKP, CPK and T3 values till did not attain normalcy, thereby demonstrating that the animals did not recover completely from dehydration stress.